27.6k views
0 votes
If Vector A is (6, 4) and Vector B is (-2, -1), what is the resultant?

2 Answers

2 votes

Answer:

(4, 3).

Step-by-step explanation:

You just add the 2 components of the vectors.

(6,4) + (-2, -1) = (6 + -2, 4 + -1)

= (4, 3).

User Vadim
by
5.7k points
2 votes

Answer:

The resultant for given Vector A is (6, 4) and Vector B is (-2, -1) is 9.43.

Step-by-step explanation:

The quantities which have both magnitude and direction is called vector.

The resultant is given by the formula:


R=\sqrt{\left(x_(2)-x_(1)\right)^(2)+\left(y_(2)-y_(1)\right)^(2)}

Where,

R is resultant of the vectors A and B


x_1,
x_2,
y_1, and
y_2 are the vertices of vectors.

Given that:


x_1=6


x_2=-2


y_1=4


y_2=-1

On substituting the given values in the above mentioned equation.


\Rightarrow R=\sqrt{(-2-6)^(2)+(-1-4)^(2)}


\Rightarrow R=\sqrt{(-8)^(2)+(-5)^(2)}


\Rightarrow R=√(64+25)


\Rightarrow R=√(89)


\therefore R=9.43

Therefore, resultant is 9.43 for the given vectors A and B.

User Jacquetta
by
4.9k points